Program Pembuatan Virgin Coconut Oil (VCO) di Desa Muara Penimbung Ilir Sebagai Pemberdayaan Masyarakat - Dwirini Dwirini; Relasari Relasari; Abukosim Abukosim; Meita Rahmawati; Ruth Samantha (Wahana Dedikasi : Jurnal PkM Ilmu Kependidikan, 2021)
Empowerment comes from the word "power" which gets the prefix "em" to become the word "empowered" which means having or having power/strong. The word "empowerment" in the English translation is "Empowerment", which comes from the word "power" which means the power to do, achieve, perform or enable. The prefix "em" can mean the power in humans, a source of creativity. Community empowerment refers to the ability of people, especially vulnerable and weak groups so that they have the strength/ability to create alternative economic actions. The purpose of this service activity is to encourage and have an economic impact, including community involvement in the Virgin Coconut Oil (VCO) production program by managing coconut into pure oil. The result of this community service is an increase in knowledge, understanding and utilization of virgin coconut oil or VCO.